Simple and Accurate Spectrofluorimetric Method for Detecting Citrinin in Red Fermented Rice. (12th June 2020) - Sun, Min; Li, Suwen; Xu, Jiahao; Zhou, Yibin; Fu, Ruiyan
Abstract: Citrinin (CIT)—an established public health threat—is a frequent component of red fermented rice (RFR). Although various quantitative techniques have been developed to detect citrinin in red fermented rice, most of these methods require expensive equipment and specially trained personnel. In this study, a simple and accurate spectrofluorimetric method was developed for detecting citrinin in red fermented rice. The proposed method is based on the measurement of native fluorescence of citrinin in methanol (pH 1.5) at an emission wavelength of 485 nm following excitation at 330 nm. The effect of quenching agents on red fermented rice samples was reduced to negligible levels by highly diluting the sample extraction solutions. The linearity was confirmed over the range from 0 to 0.15 μg/ml, and the limits of detection (LOD) and quantification (LOQ) of citrinin in the red fermented rice samples were 1.0 and 3.0 μg/kg, respectively. The developed method showed intra- and inter-day precision levels from 1.0% to 3.8% and recovery values between 91.6% and 95.0% at fortified levels from 10 to 100 mg/kg. The proposed method offers a good alternative to expensive high-performance liquid chromatography methods and can be used for the quality control of red fermented rice products under ordinary experimental conditions.